Characteristics of anticoagulant therapy and comorbidity related to overanticoagulation - Penning-van Beest, F J; van Meegen, E; Rosendaal, F R; Stricker, B H (Thrombosis and haemostasis, 2001)
The risk of hemorrhage when using coumarin anticoagulants sharply increases when the International Normalised Ratio (INR) is > or =6.0. We performed a prospective cohort study with a nested case-control design among 17,056 outpatients of an anticoagulation clinic to determine the incidence of overanticoagulation and to study the association between overanticoagulation and characteristics of anticoagulant therapy and comorbidity. The incidence rate of an INR > or =6.0 was 7.8 per 10,000 treatment days in prevalent users on the starting date and 22.5 per 10,000 treatment days in incident users during the study period. 300 cases with an INR > or =6.0 were compared with 302 randomly selected matched controls with an INR within the target zone. Patients on acenocoumarol had an increased risk of an INR > or =6.0 compared to patients on phenprocoumon. Regarding comorbidity, impaired liver function, congestive heart failure, diarrhea and fever were risk factors for overanticoagulation. Increased monitoring of INR values if risk factors are present or avoidance of risk factors could prevent excess anticoagulation and potential bleeding complications.